El Magnánimo, el Marqués de Santillana y el III libro del Curial. - BUTINYÀ, JÚLIA (Scripta)
The consequences of the paternity of Íñigo Dávalos on the Curial coincide with the literary approaches, although there are still unknowns, such as the unexplained persistence of the maternal figure in book III, which is dealt with here. The link of the Magnanimous with the lineage of the Aragonese Crown -reflected in Curial- is made through the most famous chivalries, from the legend of the good count of Barcelona; the chronicles continue with the king Pedro, whose Decameronian tales (X,6 y 7) solve the sentimental dynamic at the end of the III book. The relationship with Santillana affects the first half of book III, where the author, defending veracity, opposes Ponça's Comedieta. This is exposed in this prologue, is endorsed in the dream of Parnassus and it is applied "gilding" the less brilliant facts. Thus, both the negative aspects of Ponça's Comedieta and the sentimental situations that affect the leading couple, are gilded; these, through pure dialogues, traced from the Divine Comedy. The two quotes mythological from Dante in this book establish a renewing mixture moral, since Venus is not immoral and Jupiter is a mediator. The literary and moral aspects correspond, so that, in both -dorating it- and the truth is told in the form of friendly advice, as Dione recommends in an excellent speech. Finally, the Tragèdia de Lançalot of Lluís Gras is considered as the result of the memory of the Magnanimous.